A clinical evaluation of the alterations in the level of serum zinc, copper, iron, and manganese in the ischemic heart disease patients of Bangladesh - A case-control study. Issue 10 (October 2020) - Anonna, Shamima Nasrin; Ahamed, Sayed Koushik; Uddin, Md. Giash; Adnan, Md. Tarek; Uddin, S.M. Naim; Hussain, Md. Saddam; Millat, Md. Shalahuddin; Bulbul, Latifa; Bhatta, Rita; Sarwar, Md. Shahid; Rashid, Md. Mamun ur; Chowdhury, Jakir Ahmed; et al.
Abstract: Background: Ischemic heart disease (IHD) is a major cause of death globally. Countries vary in their rates, and changes have occurred over time. Nowadays, developing countries pose new public health challenges. Objectives: The objective of the present study was to appraise the alterations in the levels of serum Zn, Cu, Fe, and Mn that occur in patients with ischemic heart disease and to depict the correlations of the effects of these changes that lead to the pathogenesis of IHD. Methods: Zn, Cu, Fe, and Mn in the IHD patients were determined by Atomic Absorption Spectroscopy (AAS). Results: This study evaluated 52 patients with IHD, and 61 healthy volunteers served as controls. The primary outcomes of interest were explored regarding the correlations of the serum levels of these trace elements in patients with IHD. The secondary outcomes were explored in terms of inter-element relations to connect them with the pathogenesis of IHD. Our study found significantly reduced levels of Zn and Cu (2.50 ± 0.19 mg/L and 2.52 ± 0.17 mg/L, respectively) and an elevated level of Fe (148.97 ± 17.25 mg/L) in the patient group with IHD. The level of Mn (7.32 ± 1.23 mg/L) was elevated in the sera of the patients with ischemic heart disease (IHD) compared to healthy control subjects. Conclusion: Our results indicate strong associations of the pathogenesis of IHD with depleted serum levels of Zn and Cu and elevated Fe and Mn levels, which may provide a prognostic tool for the treatment of this concerning the disease. Abstract : Cardiology; Biochemistry; Molecular biology; Pathophysiology; Public health; Pharmacology; Clinical research; Ischemic heart disease, Case-control study, Trace elements, Pearson's correlation, Bangladesh.